Simulators for vascular access training: an integrative review (Research, Society and Development, 2022)
An ideal model for procedure training would be identical in sensitivity and accuracy to the real patient, allow multiple attempts, be available and accessible, and result in greater patient safety. The objective is to carry out an integrative review of the latest models developed for vascular access training and their importance in medical practice. For this, we used the integrative review from Pubmed and the Virtual Health Library (BVS), with texts published from 2015 to 2022. The search was performed using the following health descriptors: Simulators; Vascular access; Simulation training; Access Devices. Simulation models composed of animal tissues and synthetic materials with or without the use of virtual ultrasound technology were identified. The models were designed for venous access instruction. Faced with the advances and challenges of strategies for teaching skills, it is understood that venous access simulators can be a new educational modality for training students and health professionals. It is important to emphasize that with simulators the students take advantage of the error as a learning opportunity.